Step motor speed controller - Muhammad Fauzi, Muain (2010)
Stepper motors are used in many devices and appliances that are part of our everyday life. Sensing variables such as position, velocity or current for the purpose of control is a common problem in many industrial drive applications .Sensing signals that truly represent system variables, such as absolute shaft position, may be a difficult either because of cost or physical limitations. In such cases we must estimate all or some of the missing variables from limited measurements that may be noisy. This project summarizes and shows how to estimate rotor speed using microcontroller. The microcontroller which was used for this purpose is PIC16F84A. Programmable Interface Controller (PIC) 16F84A is use for control the rotation and speed of stepper motor by using the coding that program in software. Coil, coil, coil and coil are controlled by the software. A program in MPLAB IDE is developed to provide a coding to make a HEX file and transfer using PICkit 2 into PIC16F84A